C‐Met signalling is required for efficient postnatal thymic regeneration and repair. Issue 2 (February 2015) - Song, Yinhong; Su, Min; Panchatsharam, Pranau; Rood, Debra; Lai, Laijun
Summary We have reported that in vivo administration of the hybrid cytokine rIL‐7/HGFβ or rIL‐7/HGFα, which contains interleukin‐7 (IL‐7) and the β‐ or α‐chain of hepatocyte growth factor (HGF), significantly enhances thymopoiesis in mice after bone marrow transplantation. We have shown that the HGF receptor, c‐Met, is involved in the effect of the hybrid cytokines. To address the role of c‐Met signalling in thymocyte development and recovery, we generated conditional knockout (cKO) mice in which c‐Met was specifically deleted in T cells by crossing c‐Metft/ft mice with CD4‐Cre transgenic mice. We show here that although the number of total thymocytes and thymocyte subsets in young c‐Met cKO mice is comparable to age‐matched control (Ctrl) mice, the cKO mice were more susceptible to sub‐lethal irradiation and dexamethasone treatment. This was demonstrated by low recovery in thymic cellularity in c‐Met cKO mice after insult. Furthermore, the number of total thymocytes and thymocyte subsets was markedly reduced in 6‐ to 12‐month‐old cKO mice compared with age‐matched Ctrl mice, and the thymic architecture of 12‐month‐old cKO mice was similar to that of 20‐month‐old wild‐type mice. In addition, c‐Met deficiency reduced cell survival and the expression of Bcl‐xL in double‐positive thymocytes, and decreased cell proliferation and the expression of cyclin E and cyclin‐dependent kinase 5 in single‐positive thymocytes. Our data indicate that c‐Met signalling plays an important role in thymic regeneration after thymic insult. In addition, T‐cell‐specific inactivation of c‐Met accelerates age‐related thymic involution.